Synthesis and Spectro Scopic Study of Some Metal Transition Amino Organic Compounds with N-(2-OXO-1,2-Dihydropyrimidin-4-Ylcarbamothioyl) Acetamide (DPA) - Thuraya A. Kader, Basima M. Sarhan (Pakistan Journal of Medical & Health Sciences, 2022)
A New ligand, N-(2-oxo-1,2- Dihydropyrimidin-4- ylcarbamothioyl) Acetamide (DPA) was prepared by reaction of iso thiosyanate derivative with Cytosine. The ligand has been characterized through elemental analysis, H1 NMR, C13NMR, FT-IR, and UV Visible spectra, such ligand’s transition metal complexes have been characterized through conductivity measurement, FT-IR, UV Visible spectra and magnetic susceptibility, all the complexes of this ligand are solid crystal and molar ratio (2:1) (ligand: metal). The form of molecular for these complexes octa hedral. The general formula [M(DPA)2Cl2], where M+2 = (Mn, Co, Ni, Cu, Zn, Cd, Hg).